Iconographic Analysis of "Spring Breeze Has Awakened" Based on Irving Panofsky (Journal of Global Arts Studies, 2025)
Background: Iconography emerged in nineteenth-century art analysis as a method for decoding the meanings of artworks and their cultural associations. Although the concept was first proposed by Mallet, Panofsky’s three-stage interpretative framework later became the foundational methodology of iconographic studies. Its adaptation and development within the Chinese cultural context demonstrate its lasting academic significance and aesthetic value. Objective: This paper aims to explore the application of Panofsky’s iconographic theory following its localization and development in China. Through an iconographic analysis of the vernacular realist oil painting Spring Wind Has Awakened from the 1980s, the study seeks to provide new perspectives on the development of contemporary Chinese art. Methods: Based on Panofsky’s iconographic theory, this study employs a qualitative analytical approach to examine the symbolic meanings and cultural contexts embedded in Spring Wind Has Awakened, thereby evaluating its aesthetic significance and theoretical value. Results: The findings suggest that, after its localization and adaptation, Panofsky’s iconographic method has become an important approach in the study of Chinese art history. The method offers a new perspective for interpreting the aesthetic tendencies and cultural connotations of Chinese vernacular realist oil paintings, while also providing valuable insights into the development of contemporary art. Conclusion: The application of Panofsky’s iconographic analysis in China confirms its theoretical significance and practical utility in art historical research. Through the analysis of Spring Wind Has Awakened, this study demonstrates the unique value of iconography in revealing the intrinsic meanings and cultural connections embedded in artworks, thereby offering theoretical support and new research directions for the study of contemporary Chinese art.
Keywords: Irving Panofsky; Iconography; He Duoling; The Spring Breeze Has Awakened